Miniature Flexible Reprogrammable Microcontroller Circuits for E-Textiles - Tom Greig; Kai Yang; Russel Torah (Engineering Proceedings, 2023)
An e-textile system was developed, allowing USB reprogramming of miniature, flexible, integrated microcontroller circuits which allows for easier development of complex and configurable e-textile circuits. This prototype consisted of a series of five exposed pads on the edge of the PCB and a corresponding clip connector. Mounted onto the clip are a micro-USB port and necessary additional components to facilitate USB programming meaning that no additional components are required on the microcontroller board thus increasing flexibility. This system has the potential to make software development and reconfiguration of the e-textile easier while the small size and flexibility of the connector allow improved textile integration. This work provides a platform for future e-textile system development and increases the operational lifetime, thus reducing waste due to product obsolescence.